Diagnostic Performance of Contrast-Enhanced Ultrasound in Renal Cancer: A Meta-Analysis - Pan, Ke-Hao; Jian, Li; Chen, Wei-Jun; Nikzad, Abdul Aziz; Kong, Fang Q.; Bin, Xu; Wang, Ya-Li; Chen, Ming (Frontiers in Oncology, 2020)
Background: Contrast-enhanced ultrasound (CEUS) is an examination mode for detecting blood vessels in tissues, and it has been gradually used in the diagnosis of kidney cancer in recent years. This study explores the value of contrast-enhanced ultrasound in the clinical diagnosis of renal cancer, and provides an accurate and effective method for clinical diagnosis of renal cancer. Methods: CEUS and RCC were selected as the keywords. Searching the PubMed and Embase from 2007 to 2020, the original data were abstracted and performed heterogeneity test with the Meta-Disc software. The weighted sensitivity, specificity, positive likelihood ratio and negative likelihood ratio were calculated, as well as the summary receiver operating characteristic (SROC) curve. Further estimated the diagnostic value of CEUS in the research of renal cancer by calculating the area under the curve (AUC). The quality of evidence in researches were evaluated by QUADAS items. Meta-disc, Review Manager 5.3, and STATA 13 were used. Results: A total of 20 studies were adopted for Meta-analysis. The weighted sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were 0.97, 0.86, 6.8, 0.04 and 171, respectively; and AUC was 0.97. The results showed that there was high heterogeneity. Conclusion: CEUS technology has a good diagnostic and clinical value for renal RCC. I